Mitochondria targeting molecular transporters: synthesis, lipophilic effect, and ionic complex - Akula S. N. Murthy; Sanket Das; Tejinder Singh; Tae-Wan Kim; Nasim Sepay; Seob Jeon; Jungkyun Im (Drug Delivery, 2022)
As mitochondria are potential therapeutic targeting sites for the treatment of human diseases, delivering cytotoxic drugs, antioxidants, and imaging molecules to mitochondria can provide new therapeutic opportunities. In an attempt to develop a new mitochondria-targeting vector, we synthesized sorbitol-based molecular transporters with multiple guanidines, measured their partition coefficients, compared their targeting efficiency using fluorescent images and Pearson's correlation coefficients, and studied cellular uptake mechanisms. To increase the targeting ability of these molecular transporters to mitochondria, alanine-naphthalene as a lipophilic group was attached to the molecular transporter, which improved translocation across cellular membranes and led to higher accumulation in mitochondria. The molecular transporter was able to form an ionic complex with antibiotics, resulting in low cell viability. These data demonstrate that the molecular transporter with a lipophilic group could be utilized as a potential drug delivery vector for treating mitochondrial dysfunction.